SCIENTIFIC AND THEORETICAL FOUNDATIONS FOR THE DEVELOPMENT OF PROFESSIONAL AND TECHNOLOGICAL COMPETENCIES IN PEDAGOGICAL STAFF (TAMADDUN NURI JURNALI, 2025)
This article explores the scientific and theoretical foundations for developing professional and technological competencies among pedagogical personnel. It analyzes the requirements of modern educational processes, the level of teachers’ professional readiness, the adoption of digital technologies, and their integration into teaching practices. Furthermore, the article substantiates the necessity for continuous professional development, highlights the components of pedagogical competence, and the skills required for utilizing innovative technologies.